Investigating the Teacher’s Strategies in EFL Speaking Class - Medina Tumanggor (Research in English and Education Journal, 2018)
This study aimed at investigating the strategies used by the English teacher of SMP Methodist, Banda Aceh in teaching speaking class. It also tried to find out the teacher’s reasons why she used those strategies in teaching speaking class. A descriptively qualitative study was undertaken by observing the teaching and learning process in the classroom and interviewing the teacher in order to attain the needed data in this study. The results of the study showed that there were some strategies in communicative approach that the teacher used in teaching speaking class namely role-plays,discussion, storytelling, games. Meanwhile, to make the students speak up in the classroom was the main reason why the teacher more often used those strategies in speaking class. In conclusion, the strategies that have been used by the teacher could help the students speak up and be more active in learning English in the classroom, because all of the students were involved in the speaking activities.